(untitled) (Eurasian Journal of Philology Science and Education, 2021)
The article presents a brief biography of one of the founders of the steppe epic, who left an indelible mark in the history of our literature, Shalkiiz zhyrau, and tells how he traveled throughout the territory of Deshti-Kipchak throughout his long life, how he became famous and was recognized as the number one poet of his era, as he spent his whole life in the struggle, not pleasing to those in power of that time, he was a truthful akyn. The article says that the works of zhyrau are distinguished by their peculiar showiness, sharpness, conciseness, capacity, high artistic quality, elegance and energy. It also describes the history of collecting, publishing and researching the texts of a poetic legend, popularized among the Kazakh, Nogai and Kumyk population. It tells about the assistance Shalkiiz rendered to akyns and zhyrau who lived in subsequent periods. Zhyrau Shalkiiz, in turn, used and improved many genre samples of oral folk literature, just as most akyns of subsequent eras took as an example his heritage, his artistic methods, it is indicated that the phrases and poetic lines he used, artistic methods and some ideas are found in subsequent akyns both in the same form and in a transformed form, thereby demonstrating the traditional relationship between them. Such exchanges originate from time immemorial and continue to this day. It is proved that this is a process that makes the creativity of akyns and zhyrau richer and richer. Similar patterns of repetition are found in the works of such akyns of a later period as Bukhar, Makhambet, Abyl, Sherniyaz. Key words: zhyrau, poetic legends, text, manuscript, original, tradition